Pluralism, transnationalism, and culture in Asian law : a book in honour of M.B. Hooker - Bell, Gary F.; Hooker, M. B. (ISEAS Publishing, 2017)
"We owe much of our knowledge of legal diversity in Asia to the work of Barry Hooker, who appears early on to have appreciated its intrinsic interest and potentially global significance. His work in the field is, as the French say, incontournable; a nice combination of the unavoidable, the controlling and the greatly respected."--H.P. GlennTo honour this great scholar, this book gathers essays from admirers and friends who add their own contributions on legal pluralism, transnationalism and culture in Asia. The book opens with an account of M.B. Hooker colourful and prolific career. The au.